Toxic Trio: Zinc, Copper, and Mercury’s Effects on Earthworm Enzymes - Vaidya V. V.; Jadhav S. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The impact of heavy metal exposure on earthworm enzyme activities, specifically lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), malate dehydrogenase (MDH), glutamate dehydrogenase (GDH), xanthine oxidase (XOD), lipid peroxidation, superoxide dismutase (SOD), catalase, and glutathione-S-transferase (GST), was investigated in Perionyx excavatus. In control earthworms, LDH activities were 0.120 µmoles/mg protein/hour in the skin, 0.087 µmoles/mg protein/hour in the ovary, 0.062 µmoles/mg protein/hour in the testis, and 0.096 µmoles/mg protein/hour in the intestine. Exposure to mercuric chloride, copper sulfate, and zinc sulfate resulted in significant decreases in LDH activities by 10% to 19.35%, 4.16% to 22.58%, and 5.74% to 15%, respectively. Similarly, SDH activities declined by 10% to 23% with mercuric chloride, 6.89% to 17.91% with copper sulfate, and 4.13% to 16.66% with zinc sulfate treatments. MDH activities also decreased dramatically across all organs, with statistically significant reductions. GDH activities showed varied responses, while XOD activities uniformly decreased. Lipid peroxidation increased significantly after heavy metal exposure. SOD activities increased with mercuric chloride and copper sulfate, while catalase activities decreased with all three treatments. GST activities were significantly reduced by all treatments, particularly by mercuric chloride and copper sulfate. These findings underscore the substantial impact of heavy metal exposure on earthworm enzyme activities, suggesting potential cellular stress and metabolic disturbances.